Educational mismatch and labor earnings in Brazil. Issue 2 (2nd May 2017) - Reis, Mauricio Cortez
Abstract : Purpose: The purpose of this paper is to investigate the relationship between educational mismatch and labor earnings in Brazil, taking into account individual fixed effects. Design/methodology/approach: The empirical analysis employs longitudinal data and information provided by job analysts about the schooling required for each occupation. The latter of which is used to classify workers as undereducated, overeducated, or adequately matched. Estimates include individual fixed effects to control for time-invariant unobserved heterogeneity. Findings: Evidence indicates that one more year of overeducation increases labor earnings, but only half as strong as one more year of required schooling. The estimated effects on years of undereducation are negative, but undereducated workers earn more than adequately matched workers with the same level of education. Although, in particular, the incidence of undereducation in Brazil is much higher than reported for developed countries, the impact of over- and undereducation does not differ. Research limitations/implications: The fixed effects approach only controls for unobservable factors that are time-invariant. Also, much lower impacts using fixed effects may be due in part to attenuation bias as a consequence of measurement errors. Originality/value: This study contributes to the scarce literature on the consequences of overeducation and undereducation for labor earnings in developing countries, providing estimates that take into account individual fixed effects.